The Impact of Climate Change on the Sustainability of Tiger Prawn Cultivation in Tropical Waters - Annisa, Istiqama Maulidina (Professorline, 2024)
Global climate change has become a serious threat to the aquaculture sector, including tiger prawn (Penaeus monodon) cultivation in tropical waters. This research aims to analyze the impact of climate change on the sustainability of tiger prawn cultivation in Indonesia. The method used is a literature study and secondary data analysis from various trusted sources. The research results show that climate change has a significant impact on aquatic environmental parameters, such as increasing water temperature, changes in salinity, and ocean acidification. This condition affects the physiology, growth, and survival rate of black tiger prawns. Increasing water temperature causes stress in shrimp, reduces growth rate, and increases disease susceptibility. Changes in salinity due to erratic rainfall and rising sea levels disrupt the shrimp's osmotic balance. Ocean acidification hurts the calcification process of shrimp shells. In addition, climate change also increases the risk of natural disasters such as floods and storms, which can damage farm infrastructure. To maintain the sustainability of tiger prawn cultivation, an adaptation strategy is needed which includes improving cultivation technology, developing shrimp strains that are resistant to environmental changes, and implementing environmentally friendly cultivation practices. Further research is needed to develop more accurate climate change impact prediction models and effective mitigation strategies for the tiger prawn cultivation industry in tropical waters.